Nine steps for developing a scaling-up strategy (WHO GenevaCH, 2010)
Facilitates systematic planning for scaling up, i.e. expansion and institutionalisation of successfully tested health systems innovations to reach more people, more quickly and more sustainably; intended for programme managers, researchers and technical support agencies.
Keywords: HEALTH SERVICES